Paradigm Shift of Treating Wide Neck Aneurysm - Moosa, Aminath Shafeenaz; Bhattarai, Robin; Niraula, Kiran; Niyaf, Ali (Eastern Green Neurosurgery, 2026)
Background: The treatment of intracranial aneurysm has undergone very significant paradigm shifts in the recent decades. The continuous advancement in treatment and management have changed physician’s ability to make decisions. We reported a case of a 51-year-old male presenting with subarachnoid hemorrhage with intraventricular extension with generalized brain edema.